49.9k views
3 votes
-4(-2)+(-12)÷(+3)+-20+(+4)+(-6)​

User Satyajeet
by
5.1k points

2 Answers

1 vote

Answer:

-18

Explanation:


-4(-2)+((-12))/(+3)-20+(+4)+(-6)=8-(12)/(3)-20+4-6=8-4-20+4-6=-18

User Mordred
by
5.4k points
2 votes

Answer:

-18

Explanation:

-4(-2)+(-12)÷(+3)+-20+(+4)+(-6). [B.E.D.M.A.S rule] (First bracket)

= 8 - 12 ÷ 3 - 20 + 4 - 6. (Then division)

= 8 - 4 - 20 + 4 - 6. (Then after addition)

= 8 + 4 - 4 - 20 - 6

= 12 - 30. (At last subtraction)

= -18 (Ans)

User Mariotomo
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.